A comprehensive review on molecular dynamics simulation studies of phenomena and characteristics associated with clathrate hydrates - Sinehbaghizadeh, Saeid; Saptoro, Agus; Amjad-Iranagh, Sepideh; Naeiji, Parisa; Tiong, Angnes Ngieng Tze; Mohammadi, Amir H (2022)
Clathrate hydrates or gas hydrates have received worldwide attention due to their potential to be utilized in various sustainable technologies. The hydrate-based industrial applications as well as developing green technologies or safely extracting natural gases stored in the nature require profound comprehension of the phenomena associated with gas hydrates. On the flip side, identifying the characteristics of different hydrate formers and the effects of a wide range of introduced additives to these technologies is the critical objective, so that needs to be deeply investigated at both macroscopic and microscopic scales. The expensive experiments and limited availability of facilities at the nanoscale encourage researchers to apply novel computational methods and simulation approaches. For three decades, molecular dynamics (MD) simulations in the field of gas hydrates have been widely used to mathematically analyse the physical movements of molecules and the evolution of atomic positions in time. In this work, the mechanisms involved in the pure, binary, and mixed gas hydrates, and the impressions of promoters/inhibitors/minerals on gas hydrates were briefly reviewed. Also, the phenomena and properties associated with gas hydrates such as nucleation, growth, stability, dissociation, cage occupancy, storage capacity, morphology analysis, guest role, thermo-physical and mechanical properties, dynamical and vibrational behaviours of gas hydrates were reviewed. This work aims to provide readers with an extensive overview of MD simulations of gas hydrates to stimulate further research on this riveting field.